Pneumatic bio-soft robot module: Structure, elongation and experiment - Guanjun, Bao; Pengfei, Yao; Zonggui, Xu; Kun, Li; Zhiheng, Wang; Libin, Zhang; Qinghua, Yang (International Journal of Agricultural and Biological Engineering, 2017)
Soft robotics, often taking inspirations from biomimetics, is an exciting novel research field and has great capability to work with creatures. A new type of bio-soft robot inspired by elephant trunk and octopus was proposed, which has a promising application in robotic agricultural harvesting. The two modularized structures, basal segment and caudal segment, were elaborated in detail. They both have three side chambers and one central chamber, which are reinforced by springs for better stretch performance in axial direction without radial expansion. All the chambers can act as drivers when inflated with compressed air. More importantly, the central chamber was designed for regulating the stiffness of the robot module as needed in application. The primary static model for axial elongation was established for the fundamental analysis of the bio-soft robot module’s features, such as iso-force, isobaric and isometric characteristics. Simulation and experimental results showed that the motion of the proposed bio-soft module has approximate linearity in iso-force and isobaric conditions, and strict linearity in isometric condition. Keywords: bio-soft robot, pneumatic muscle actuator, static model, harvesting robot DOI: 10.3965/j.ijabe.20171002.2909 Citation: Bao G J, Yao P F, Xu Z G, Li K, Wang Z H, Zhang L B, et al. Pneumatic bio-soft robot module: Structure, elongation and experiment. Int J Agric & Biol Eng, 2017; 10(2): 114–122.